Visual policy narrative messaging improves COVID-19 vaccine uptake. Issue 4 (18th April 2023) - Shanahan, Elizabeth A; DeLeo, Rob A; Albright, Elizabeth A; Li, Meng; Koebele, Elizabeth A; Taylor, Kristin; Crow, Deserai Anderson; Dickinson, Katherine L; Minkowitz, Honey; Birkland, Thomas A; Zhang, Manli
Abstract: In the face of vaccine hesitancy, public health officials are seeking more effective risk communication approaches to increase vaccination rates. We test the influence of visual policy narratives on COVID-19 vaccination behavior through a panel survey experiment conducted in early 2021 ( n = 3, 900) and then 8 weeks later ( n = 2, 268). We examine the effects of three visual policy narrative messages that test the narrative mechanism of character selection ( yourself, your circle, and your community ) and a nonnarrative control on COVID-19 vaccine behavior. Visual risk messages that use narratives positively influence COVID-19 vaccination through serial mediation of affective response to the messages and motivation to get the COVID-19 vaccination. Additionally, character selection matters, as messages focusing on protecting others (i.e. your circle and your community ) perform stronger than those of yourself . Political ideology moderated some of the effects, with conservative respondents in the nonnarrative control condition having a higher probability of vaccination in comparison to the protect yourself condition. Taken together, these results suggest that public health officials should use narrative-based visual communication messages that emphasize communal benefits of vaccinations.